2015
DOI: 10.1210/jc.2014-2932
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin Levels Are Regulated by Acute Strenuous Exercise

Abstract: We show that irisin levels are affected by age, sex, obesity, and particularly muscle mass, whereas diurnal rhythm and meals do not contribute to the variation in irisin levels. Short bouts of intensive exercise but not long-term elevations in physical activity, acutely and transiently increase serum irisin levels in children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
153
5
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 37 publications
14
153
5
14
Order By: Relevance
“…The level of irisin was found to be increased after acute exercise as expected, however, irisin levels were found to be decreased after chronic exercise training [12,13].…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…The level of irisin was found to be increased after acute exercise as expected, however, irisin levels were found to be decreased after chronic exercise training [12,13].…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…Also, the browning formation that Irisin may cause could lead to reduced weight gain, up-regulated insulin sensitivity, reduced risk of diabetes type II and other metabolic disorders as animal studies indicate [89][90][91][92][93] , as well as increase daily resting energy expenditure in humans 94,95 . However, the secondary outcomes of our systematic review shows that even when Irisin was measured with the same ELISA (PP, EK-067-52) there was no relationship 22 or a positive relationship with resting energy expenditure 37 , and no association 72 or a positive association with BMI 71 . This specific ELISA kit (PP, EK-067-52) has been tested by a previous study for validity 27 , which showed it to be invalid for circulating Irisin identification.…”
Section: Quality Of Evidence and Limitationsmentioning
confidence: 76%
“…The 24-h serum profiles of the bone markers and levels after a bout of acute strenuous exercise [21] were assessed in 4 young adults with no reported chronic disease (2 lean individuals [BMI 20.5–21.2] aged 20 and 21 years and 2 obese individuals [BMI 35.5 and 35.7] aged 32 and 34 years.…”
Section: Methodsmentioning
confidence: 99%